Capillary electrophoresis as a tool for genotyping SH3 mediated coffee leaf rust resistance (Scientia Agropecuaria, 2021)
Coffee is an important agricultural commodity in the world. However, it is susceptible to Hemileia vastatrix (Hv), an obligatory biotrophic fungus that causes coffee leaf rust (CLR). Natural resistance to rust has been identified in the wild species Coffea canephora and Coffea liberica. These species have been used in breeding programs where interspecific resistant hybrids have been generated. The SH3 gene, derived from C. liberica, has been shown to confer extreme and long-lasting resistance to Hv. A total of 167 accessions of the INIA’s Coffee Germplasm Collection of Peru (INIA-CGC) were screened with 4 markers linked to the SH3 gene. As positive controls, EA67 (C. liberica) and the hybrid S.288 (C. arabica x C. liberica) were used. Separation of PCR products was done by capillary electrophoresis, which allow to discriminate the alleles of each marker. For three markers, specific alleles for either C. arabica or C. liberica species were found. In all cases, S.288 exhibited specific alleles for both species; whereas the INIA-CGC accessions had exclusively C. arabica alleles and EA67 had C. liberica alleles. The BA-48-21O-f marker did not produce PCR fragments for any of the positive controls, suggesting that this marker is not as predictive as the other three to determine the presence of SH3. This work reports the existence of multiple alleles for the Sat244 marker; however, the collection does not have the SH3 mediated-resistance gene. Finally, the utility of capillary electrophoresis as a tool to identify alleles linked to SH3 was demonstrated.